Morning-types are prevalent in athletes participating in individual sport - Rae, D. E.; Kunorozva, L.; Stephenson, K. J.; Roden, L. C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Recently, a link between an individual`s diurnal preference (i.e. chronotype) and a variable number tandem repeat (VNTR) polymorphism in the Period 3 gene (PER3) has been demonstrated. The longer PER35 and shorter PER34 alleles have been associated with a preference for mornings and evenings respectively. The extent to which this chronotype-genotype relationship exists in athletic populations has not been determined. Methods: Caucasian, male cyclists (CYC, n=125, 37.2±7.1 years old, 9.5±7.1 years training), runners (RUN, n=120, 35.6±7.1 years old, 9.4±7.1 years training), Ironman triathletes (IM, n=287, 36.8±6.5 years old, 2.2±1.8 years training) and a control population of active, non-competitive individuals (CON, n=96, 32.9±8.1 years old, 6.1±6 years of training) participated in this study. The chronotypes of all CYC, RUN and CON participants and a sub-sample of the IM group (n=49) were assessed using the HorneÖstberg Morningness-Eveningness Personality Questionnaire. The PER3 VNTR genotype for each participant was determined by a PCRbased test using DNA extracted from buccal or blood samples. Results: The CYC, RUN and IM groups contained more morning-type individuals (CYC: 79%; RUN: 72%; IM: 65%) than the control group (42%, p<0.001). Furthermore, the athletic populations contained more individuals genotyped as PER35/5 - i.e. homozygous for the "morning-type" allele - (CYC: 41%; RUN: 23%; IM: 28%) than the control group (9%, p<0.001). The prevalence of the PER35 allele was greater in the athlete groups (CYC: 61%, RUN: 58%, IM: 56%, p<0.001) than the control group (38%, p<0.001), and differed from reported frequencies in other populations world-wide. When the data from all four groups were pooled, a strong relationship between chronotype and PER3 VNTR genotype was observed (p<0.001). Finally, the time of day at which the athletes preferred to train was related to their chronotype (p<0.001). Of all the morning-types in this study 77% reported preferring to train in the morning. Similarly, 79% of the evening-types preferred to train in the evenings. Discussion: This is the first study to demonstrate the chronotype-PER3 VNTR genotype association in an athletic population. Based on our data, Caucasian males participating in individual endurance sports with early start times in South Africa are more likely to be morning-type individuals. Furthermore, the PER3 VNTR may be one of the factors contributing to this observation. Future investigation into the relationships between chronotype, genotype, performance and efficacy of training time of day is warranted.